Cost-utility of biological treatment sequences for luminal Crohn's disease in Europe. (2nd November 2017) - Rencz, Fanni; Gulácsi, László; Péntek, Márta; Gecse, Krisztina B.; Dignass, Axel; Halfvarson, Jonas; Gomollón, Fernando; Baji, Petra; Peyrin-Biroulet, Laurent; Lakatos, Peter L.; Brodszky, Valentin
ABSTRACT: Background : This study aims to compare the cost-effectiveness of treatment sequences with available biologics, including adalimumab (ADA), biosimilar infliximab (bsIFX), originator infliximab (IFX) and vedolizumab (VEDO) for luminal Crohn's disease in nine European countries. Methods : A Markov-model was constructed to simulate five-year medical costs and quality-adjusted life years (QALYs). Data on clinical efficacy were obtained from randomised controlled trials. Country-specific unit costs, discount rates and a third-party payer perspective were applied. Results : The bsIFX versus conventional therapy resulted in the most favourable incremental cost-utility ratios (ICURs) ranging from €34, 580 (Hungary) to €77, 062/QALY (Sweden). Compared to bsIFX, the bsIFX-ADA sequence was more cost-effective than the bsIFX-VEDO sequence with ICURs varying between €70, 277 (France) and €162, 069/QALY (Germany). The ICURs of the bsIFX-ADA-VEDO sequence versus the bsIFX-ADA strategy were between €206, 266 (The Netherlands) and €363, 232/QALY (Spain). Conclusion : We are the first to compare cost-effectiveness of multiple biological sequences for luminal Crohn's disease. Based on our findings, bsIFX can be recommended as a first-line treatment in patients unresponsive to conventional treatments. While biological sequences only slightly differ in their associated health gains, their costs vary greatly. The bsIFX-ADA-VEDO seems to be the most cost-effective sequence of the available biologics across Europe.